Pengaruh Media Sosial "Tiktok" Terhadap Wawasan Kebangsaan pada Generasi Muda - Azkiya Lisdinani; Azmi Noer Afifah; Chintia Restiana; Muhammad Bintang Alief Al Daffa; Supriyono Supriyono (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The use of TikTok for younger ages can increase cooperation between users without being limited by distance and time. The simplicity of association has an impact on the ease of delivery, both the delivery of news / messages and the provision of reactions in the form of analysis and ideas. One of the adverse effects that can occur is the delivery of the message as a challenge to silence insulting discourse related to social and state life. At Stiepar Yapari Aktripa Bandung, research was conducted to see how TikTok affects the sense of national identity of the younger generation. For this reason, information about the Pancasila tribe is very important in the existence of the younger generation with the spread of data in developed countries. Further research is expected to determine the influence of TikTok on people's knowledge among the younger generation. This exploration could include directing studies or meetings with younger generations to understand their perspectives on public issues and how TikTok might influence their point of view. The research can also look at how younger generations perceive TikTok videos about national issues and their content.